Decellularized extracellular matrix derived from dental pulp stem cells promotes gingival fibroblast adhesion and migration - Nunthawan Nowwarote; Zakaria Chahlaoui; Stephane Petit; Lucas T. Duong; Florent Dingli; Damarys Loew; Ajjima Chansaenroj; Chatvadee Kornsuthisopon; Thanaphum Osathanon; Francois Come Ferre; Benjamin P.J. Fournier (BMC, 2024)
Abstract Background Decellularized extracellular matrix (dECM) has been proposed as a useful source of biomimetic materials for regenerative medicine due to its biological properties that regulate cell behaviors. The present study aimed to investigate the influence of decellularized ECM derived from dental pulp stem cells (DPSCs) on gingival fibroblast (GF) cell behaviors. Cells were isolated from dental pulp and gingival tissues. ECM was derived from culturing dental pulp stem cells in growth medium supplemented with ascorbic acid. A bioinformatic database of the extracellular matrix was constructed using Metascape. GFs were reseeded onto dECM, and their adhesion, spreading, and organization were subsequently observed. The migration ability of the cells was determined using a scratch assay. Protein expression was evaluated using immunofluorescence staining. Results Type 1 collagen and fibronectin were detected on the ECM and dECM derived from DPSCs. Negative phalloidin and nuclei were noted in the dECM. The proteomic database revealed enrichment of several proteins involved in ECM organization, ECM-receptor interaction, and focal adhesion. Compared with those on the controls, the GFs on the dECM exhibited more organized stress fibers. Furthermore, cultured GFs on dECM exhibited significantly enhanced migration and proliferation abilities. Interestingly, GFs seeded on dECM showed upregulation of FN1, ITGB3, and CTNNB1 mRNA levels. Conclusions ECM derived from DSPCs generates a crucial microenvironment for regulating GF adhesion, migration and proliferation. Therefore, decellularized ECM from DPSCs could serve as a matrix for oral tissue repair.